ANALISIS KINERJA DAN RELASI BUPATI GROBOGAN DENGAN DPRD KABUPATEN GROBOGAN DALAM KEKOSONGAN WAKIL BUPATI GROBOGAN PERIODE 2016-2019 - Ivan - Bahtiar; Kushandajani - - (Journal of Politic and Government Studies, 2020)
Indonesia is a democratic country and knows a government system where a leader and his representative are elected by the public directly through elections. Election is a democratic party or people's party which becomes an arena of competition to fill political positions in government based on the formal choice of citizens who meet the requirements. Election of regional heads (Pilkada) directly held in the country since 2005, provides ample opportunity for voters to make their choices according to the wishes and conscience of each in the region. In the 2015 elections there were only two candidates, namely incumbent candidate number 1 pair H. Icek Baskoro, S.H., M.H. and H. Sugeng Prasetyo, S.E., M.M. is the Incumbent Deputy Regent of Grobogan, and sequence number 2 is Sri Sumarni, S.H., M.M. and Edy Maryono, S.H., M.M. who were former candidates for the previous Regent. Regent of Grobogan Hj. Sri Sumarni, S.H., M.M. in carrying out the duties of government by themselves or 'single leader'. Within the leadership of Grobogan Regent Hj. Sri Sumarni, S.H., M.M. carrying out his administrative duties assisted by regional secretaries and staff in the government. As Regional Head Mrs. Hj. Sri Sumarni, S.H., M.M. in his government he made many changes in his leadership. The research method used by researchers is a qualitative research method. The results of the study are related to the analysis of the performance and relations of the Grobogan Regent with the Grobogan District DPRD in the Grobogan District Deputy vacuum in the 2016-2019 period in this study. Researchers try to dig data about performance by using indicators of productivity, service quality, responsiveness, responsibility and accountability and analysis of power relations. The performance of the Grobogan Regent in the vacancy of the Deputy Grobogan Regent in the 2016-2019 Period can be said to be successful in referring to the results of the rapid increase in regional development.